(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
The World Trade Organization’s Dispute Settlement Understanding (DSU) established a unique, compulsory, rule-based system of inter-state commercial dispute resolution. Over three decades the system-building yielded rich jurisprudence, high measured compliance and broad usage by both developed and developing Members. Since 2017-2019, however, the system has been subjected to deep structural stress: long delays in time-consuming cases, doctrinal drift in the Appellate Body (AB) as Members perceive it, and de facto paralysis of the AB since December 2019. These tendencies catalysed alternative modalities (such as the Multi-Party Interim Appeal Arbitration — MPIA) and political showdown over substantive judicial powers. This paper assesses legal effectiveness by combining empirical numbers with leading jurisprudence and analysis of doctrine and then proposes legally-possible reforms that are politically-viable. The analysis takes special consideration of accession candidates and middle income Members (with Uzbekistan as an illustrative domestic-law comparator), and concludes by sketching a prioritised reform agenda addressing appellate review, procedural promptness, compliance entitlements and capacity enhancement.